Characterisation of mechanical and thermal properties in flax fabric reinforced geopolymer composites - Assaedi, H.; Alomayri, Thamer Salman F; Shaikh, Faiz; Low, It Meng (SpringerOpen, 2015)
This paper presents the mechanical and thermal properties of flax fabric reinforced fly ash based geopolymer composites. Geopolymer composites reinforced with 2.4, 3.0 and 4.1 wt% woven flax fabric in various layers were fabricated using a hand lay-up technique and tested for mechanical properties such as flexural strength, flexural modulus, compressive strength, hardness, and fracture toughness. All mechanical properties were improved by increasing the flax fibre contents, and showed superior mechanical properties over a pure geopolymer matrix. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) studies were carried out to evaluate the composition and fracture surfaces of geopolymer and geopolymer/flax composites. The thermal behaviour of composites was studied by thermogravimetric analysis (TGA) and the results showed significant degradation of flax fibres at 300 °C.